The Mediating Roles of Rejection Sensitivity and Proximal Stress in the Association Between Discrimination and Internalizing Symptoms Among Sexual Minority Women. - Dyar, Christina; Feinstein, Brian A.; Eaton, Nicholas R.; London, Bonita (Archives of Sexual Behavior, 2018)
The negative impact of discrimination on mental health among lesbian, gay, and bisexual populations has been well documented. However, the possible mediating roles of sexual orientation rejection sensitivity and rejection-based proximal stress in the association between discrimination and internalizing symptoms remain unclear. Rejection-based proximal stress is a subset of proximal stressors that are theorized to arise from concerns about and expectations of sexual orientation-based rejection and discrimination. Drawing on minority stress theory, we tested potential mediating effects using indirect effects structural equation modeling in a sample of 300 sexual minority women. Results indicated that the indirect effect of discrimination on internalizing symptoms (a latent variable indicated by depression and anxiety symptoms) through sexual orientation rejection sensitivity and rejection-based proximal stress (a latent variable indicated by preoccupation with stigma, concealment motivation, and difficulty developing a positive sexual identity) was significant. Additionally, the indirect effects of discrimination on rejection-based proximal stress through sexual orientation rejection sensitivity and of sexual orientation rejection sensitivity on internalizing symptoms through rejection-based proximal stress were also significant. These findings indicate that sexual orientation rejection sensitivity plays an important role in contributing to rejection-based proximal stress and internalizing symptoms among sexual minority women.